(3TQM GdJfXje GdbGfhfj ddVQjHI GdYGeI Ydi GdeHjYGJ hdGFMJg GdJfajPjI (B/s - (3GHQGgje, CMeO YHO GddWjas ((3GdbGgQI(B: s (3GdecJH GdKbGaj(B;(3OGQ GdCSeGM(B, s, 2004)
(3TQM GdeGOI GdSGOSI hGdYTQhf Edi ZGjI GdCQHYhf TQM GdeGOI GdMGOjI hGdCQHYhf Edi ZGjI GdMGOjI hGdNeShfs
Keywords: (3GdbGfhf GdJLGQjs; (3GdeHjYGJ(B- (3GdVQGFHs